Satellite Geodesy Captures Offset Magma Supply Associated With Lava Lake Appearance at Masaya Volcano, Nicaragua. Issue 6 (28th March 2018) - Stephens, K. J.; Wauthier, C.
Abstract: Ascending and descending Interferometric Synthetic Aperture Radar data sets from various satellites (CSK, RSAT‐2, ALOS‐2, and Sentinel‐1) show a maximum of ∼8 cm ground inflation in Masaya caldera over a 10 month period (6 November 2015 to 1 September 2016). The center of inflation is located in the NW part of the caldera, north of the active Santiago vent which has hosted a new lava lake since 11 December 2015. Simultaneous inversions of those Interferometric Synthetic Aperture Radar data sets using a neighbourhood algorithm demonstrate that a spherical magma reservoir explains the geodetic data, with a horizontal location ∼3 km north of the active Santiago vent and a depth‐to‐center ∼3 km. The associated modeled volume increase (∼0.0042 km 3 ) is lower than the "excess" magma volume inferred from gas measurements from November 2015 to February 2016. The magma reservoir offset from the current center of eruptive activity may be the result of preexisting caldera structures. Key Points: InSAR captures ground inflation coincidently with appearance of lava lake in late 2015 Major magma supply is offset 3 km north of active vent at Masaya Modeled magma supply is consistent with independent gas measurements